Improved bioethanol production from oil palm trunk sap - Rossyuhaida, Mohd Zakria (2015)
Renewable energy such as bioethanol produced from biomass waste is gaining a lot of interest worldwide due to depletion of fossil fuel reserve. The OPT felled for replanting is a suitable raw material to produce bioethanol because it is an abundant waste material produced by the palm oil industry in Malaysia. In order to utilize the felled OPT, fermentation by suitable microorganism can be performed to obtain bioethanol. Hence, this study was carried out to select the best microorganisms for bioethanol fermentation using OPT sap and to optimise nutrient supplementation in OPT sap for bioethanol fermentation. In this study, four microorganisms were tested for ethanol production at fixed temperature, pH, agitation and inoculum size which are Saccharomyces cerevisiae ATCC 9763, Saccharomyces cerevisiae CCT 0762, dry baker’s yeast and Kluyveromyces marxianus ATCC 46537. The parameters were set at inoculum size of 10 % (v/v), agitation speed of 150 rpm, incubation temperature of 30 ºC and fermentation time of 72 hours. Two types of analytical method were performed to analyse the data which are cell dry weight measurement and High Performance Liquid Chromatography (HPLC). The results showed that K. marxianus ATCC 46537 produced the highest ethanol yield (0.39 g/g) at a shorter fermentation time (16 h) compared to the other strains. Then, response surface methodology (RSM) was employed to optimise the nutrient supplementation in OPT sap. Using Two-level Factorial Design, six nutrients, namely ammonium sulphate, di-ammonium hydrogen phosphate, magnesium sulphate, β-alanine, calcium chloride and potassium dihydrogen phosphate were screened using K. marxianus ATCC 46537 and the selected significant nutrients were magnesium sulphate and β-alanine. Subsequently, the optimisation study using Central Composite Design found the optimum value of magnesium sulphate was 7.93 g/L and 0.90 g/L for β-alanine. Under optimum conditions, the predicted ethanol concentration was 0.46 g/g while the experimental value (0.47 g/g) was in agreement with the predicted value with 2.13 % error. As a conclusion, K. marxianus ATCC 46537 were able to improve ethanol production from 0.39 g/g without nutrient supplementation into 0.47 g/g with nutrient optimisation using RSM.